2017
DOI: 10.17509/wapfi.v2i2.8280
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Experiential Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa

Abstract: Berdasarkan hasil observasi menunjukkan bahwa keterampilan berpikir kritis siswa masih rendah. Oleh karena itu, keterampilan berpikir kritis siswa perlu ditingkatkan khususnya pada materi fluida statis, maka diterapkan model experiential learning. Model experiential leraning mengajak siswa untuk berperan aktif selama proses pembelajaran dengan mengembangkan pengalaman-pengalaman siswa. Tujuan penelitian ini untuk mengetahui keterlaksanaan pembelajaran menggunakan model experiential learning dan peningkatan ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
(4 reference statements)
1
8
0
6
Order By: Relevance
“…The increasing of geography learning scores in students applying experiential learning was due to the syntax of learning that was students observing and reflecting (Mallawaarachchi et al, 2018). This stage was thought to stimulate students' critical thinking abilities towards real-life experiences and able to improve students abilities in reading comprehension (Nurhasanah et al, 2017;Syafrizal et al, 2019). Besides the observation and reflection stages, another syntax that is able to improve student learning outcomes was the conceptualization syntax.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing of geography learning scores in students applying experiential learning was due to the syntax of learning that was students observing and reflecting (Mallawaarachchi et al, 2018). This stage was thought to stimulate students' critical thinking abilities towards real-life experiences and able to improve students abilities in reading comprehension (Nurhasanah et al, 2017;Syafrizal et al, 2019). Besides the observation and reflection stages, another syntax that is able to improve student learning outcomes was the conceptualization syntax.…”
Section: Discussionmentioning
confidence: 99%
“…Experiential learning places more emphasis on solving authentic problems that occur daily through hands-on learning experiences with the teacher as a guide (Baidowi et al, 2015). Experiential learning has a significant influence on students' critical and creative thinking skills (Kurniawan et al, 2019;Nurhasanah et al, 2017). Like the SCAMPER technique with fun learning able to develop students' creative thinking (Ozyaprak,2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, this learning extends beyond formal education and becomes very important in self-managed continuing professional development [? ] The importance of involving students in cooperative learning conducted by S. Nurhasanah [5]. According to S. Nurhasanah that results of research during three meetings showed increased activity of teachers and students every encounter with an average 92.15% excellent category.…”
Section: Introductionmentioning
confidence: 99%
“…Perubahan dalam pembelajaran sesuai era 4.0 akan berdampak pada peran pendidikan khususnya peran pendidik. Kondisi tersebut harus diatasi dengan menambah kompetensi pendidik yang mendukung eksplorasi dan penciptaan melalui pembelajaran mandiri (Triyono, 2017 (Nurhasanah, et al, 2017).…”
unclassified